On-farm evaluation of production potential and economics of Wheat-Jute-T.aman rice-based cropping system - Kamrozzaman, MM; Khan, MAH; Ahmed, S; Quddus, AFM Ruhul (Journal of the Bangladesh Agricultural University, 2016)
The study was conducted to determine the yield and economic consequences of two cropping patterns viz. improved cropping pattern (Wheat-Jute-T.aman rice) and farmers, pattern (Wheat-Jute-T.aman rice) through incorporation of modern high yielding varieties and improved management practices for crop production. The experiment was laid out in randomized complete block design with five dispersed replications in farmers condition in Faridpur during two consecutive years 2011-12 and 2012-13. Two years mean data showed that the improved management practices for the pattern provided significantly higher yield in Wheat, Jute and T.aman rice. The gross return (Tk. 265495/ha) and net return (Tk.123087/ha) of improved pattern were 9 % and 18 % higher, respectively compared to that of farmers pattern with only 3% extra cost. The higher benefit cost ratio, land use efficiency, production efficiency and sustainable yield index indicated the superiority of the improved pattern over the farmers practices. J. Bangladesh Agril. Univ. 13(1): 93-100, June 2015